A HISTORICAL CRITIQUE ON GRAPHIC ART THROUGH MODERNISM WITH SPECIAL REFERENCE TO BENGAL DURING PRE-INDEPENDENCE PERIOD - Khanra, Sanjay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article was examining the emergence of woodcut as a primary medium of modern art during the pre-independence period, dubbed "the woodcut revolution in Bengal" by Manindrabhusan Gupta. In graphic art history, the resurgence of antiquated media like lithography, etching, and woodcut was a significant feature that distinguished modernism, challenging the notion of progress and the techno-economic constraints that governed the creation of visual images. Halftone had totally overtaken lithography as a popular commercial medium by the time Gaganendranath released his lithographic album, Atvut Lok, in 1917. Rather than opting for lithography, he could have opted for halftone printing, a strategy he had previously employed for his popular cartoon album Birup Bajra, which saw widespread distribution. This droves him to build a new studio setup in his home and hire a lithographer with experience to assist him. His costly and time-consuming choice to print the record in lithography demonstrated his modernism and his preference for the medium’s aesthetic value over its practicality. In this article, a historical critique on graphic art through modernism with special reference to Bengal during pre-independence period has been discussed.